Tephrostratigraphy and Provenance From IODP Expedition 352, Izu‐Bonin Arc: Tracing Tephra Sources and Volumes From the Oligocene to Recent. (20th January 2018) - Kutterolf, S.; Schindlbeck, J. C.; Robertson, A. H. F.; Avery, A.; Baxter, A. T.; Petronotis, K.; Wang, K.‐L.
Abstract: Provenance studies of widely distributed tephras, integrated within a well‐defined temporal framework, are important to deduce systematic changes in the source, scale, distribution, and changes in regional explosive volcanism. Here, we establish a robust tephrochronostratigraphy for a total of 157 marine tephra layers collected during IODP Expedition 352. We infer at least three major phases of highly explosive volcanism during Oligocene to Pleistocene time. Provenance analysis based on glass composition assigns 56 of the tephras to a Japan source, including correlations with 12 major and widespread tephra layers resulting from individual eruptions in Kyushu, Central Japan, and North Japan between 115 ka and 3.5 Ma. The remaining 101 tephras are assigned to four source regions along the Izu‐Bonin arc. One, exclusively assigned to the Oligocene age, is proximal to the Bonin Ridge islands; two reflect eruptions within the volcanic front and back‐arc of the central Izu‐Bonin arc, and a fourth region corresponds to the Northern Izu‐Bonin arc source. First‐order volume estimates imply eruptive magnitudes ranging from 6.3 to 7.6 for Japan‐related eruptions and between 5.5 and 6.5 for IBM eruptions. Our results suggest tephras between 30 and 22 Ma reflect a subtly different Izu‐Bonin chemical signature compared to the recent arc. After a ∼9 Ma gap in eruption, tephra supply from the Izu‐Bonin arc predominated from 15 to 5 Ma, and finally a subequal mixture of tephra sources from the (palaeo)Honshu and Izu‐Bonin arcs occured within the last ∼5 Ma. Plain Language Summary: Provenance studies of widely distributed tephras, integrated within a well‐defined temporal framework, are important to deduce systematic changes in the source, scale, distribution, and changes in regional explosive volcanism. Here, we establish a robust tephrochronostratigraphy for marine tephra layers collected during IODP Expedition 352, assigning the eruptions to both sources from the Japan mainland and the Izu‐Bonin arc. Using correlations with individual eruptions in Japan, we have also estimated respective eruptive volumes and eruption magnitudes. Together with marine tephras assigned to provenance regions within the Izu‐Bonin arc system, this indicates for the first time how large eruptions from the source regions must have been in the past in this region. The tephra record additionally provides glimpses of the history of explosive volcanism on the Izu‐Bonin arc system back to the Oligocene and also helps to indicate how this relates to explosive volcanism in Japan. Key Points: A Holocene to Oligocene tephrochronostratigraphy has been developed for IBM and Japan tephras At least three major phases of highly explosive volcanism during Oligocene to Pleistocene time with, variable sources from Japan and IBM arcs Assigning source regions and volume estimates for IBM eruptions and refining eruptive volumes for 12 correlated Japanese eruptions